IMPACT OF NUTRIENT MANAGEMENT OF ZIZYPHUS MAURITIANA (LAMB.) ON THE YIELD OF KUSMI LAC - B. K. NAMDEV; M. THOMAS; A. KURMI,; A. S. THAKUR; A. UPADHYAYA (The Bioscan, 2015)
Lac production is a major economic activity of rainfed farmers in Seoni district, Madhya Pradesh. In the district lac production is carried on both Butea monosperma and Zizyphus mauritiana plants. The lac productivity is low due to no nutrient management of these host trees. The study impact of nutrient management of Z. mauritiana on the yield of Kusmi lac was conducted in Dhapara village, Barghat Block, Seoni District, MP from May 2013 to February 2014. The trial consisted on forty eight Z. mauritiana plants with four treatments (basal application of Urea- T1, Urea and SSP-T2, Urea, SSP and MOP- T3, and control- T4) and six replications. The results revealed that the mean weight of 100 fresh cells of lac at harvest as well as the dry cell weight increased significantly in nutrient treated Z. mauritiana plants as compared to the control. The highest increase in the mean fresh weight of 100 cells over the control in was T3 (30.61%) followed by T1 (17.26%) and T2 (12.21%). Similarly the mean dry weight of 100 cells was highest in T3 (36.63%) followed by T1 (21.62%) and T2 (16.02%) over the control respectively. The mean yield of Kusmi lac per Z. mauritiana was highest in T3 (39.16%) followed by T1 (32.63%) and T2 (18.53%) over the control. The yield of Kusmi lac (kg) per Z. mauritiana was 5.08, 4.54, 5.33 and 3.83kg respectively among the different treatments T1, T2, T3, and T4. Thus the nutrient management of Z. mauritiana for lac production significantly increased the yield up to 39.16 percent.